Decreased CD57 expression of natural killer cells enhanced cytotoxicity in patients with primary sclerosing cholangitis - Liu, Bin; Yang, Guo-Xiang; Sun, Ying; Tomiyama, Takashi; Zhang, Weici; Leung, Patrick S. C.; He, Xiao-Song; Dhaliwal, Sandeep; Invernizzi, Pietro; Gershwin, M. Eric; Bowlus, Christopher L. (Frontiers in Immunology, 2022)
Background/Aims Primary sclerosing cholangitis (PSC) is a chronic inflammatory biliary disease for which the immunopathological basis remains an enigma. Natural killer (NK) cells are key components of innate immunity and seemingly play opposite roles in autoimmune disease (AID). The aim of this study is to determine the role of NK cells in the pathogenesis of PSC. Methods The frequency and phenotype of circulating NK cells in a large cohort of patients with PSC and healthy controls (HC) were systematically examined. In addition, the functional capacity of NK cells including cytotoxicity and cytokine production were studied. Results The frequency of CD3-CD56dimCD16+ (defined as CD56dim) NK cells in PSC patients was significantly lower in comparison to HC. CD56dim NK cells from PSC displayed a more immature phenotype including high expression of the natural killing receptor NKp46 and down regulation of the highly differentiated NK cells marker CD57. Interestingly, the reduction of CD57 expression of NK cells was associated with PSC disease severity. In addition, PSC CD56dim NK cells exhibited increased CD107a degranulation and cytolytic activity towards target cells compared with HC. Further analysis demonstrated that CD57-CD56dim NK cells from PSC had elevated expression of NKp46, NKp30, IL-2 receptor, KLRG1 and higher cytotoxic capacity compared to CD57+CD56dim NK cells. Conclusions Our data demonstrate that the differentiation of PSC NK cells is dysregulated with enhanced cytotoxic activity. This change is likely to be functionally involved in pathogenesis and disease progression, highlighting the potential of NK-directed immunotherapy for PSC.